[tex]\frac{9}{11} - \frac{3}{11} = \frac{6}{11}[/tex]
[tex]\frac{3}{16} - \frac{1}{16} = \frac{2}{16} = \frac{1}{8}[/tex]
[tex]1 - \frac{3}{8} = \frac{8}{8} - \frac{3}{8} = \frac{5}{8}[/tex]
[tex]4 - \frac{2}{5} = 3\frac{5}{5} - \frac{2}{5} = 3\frac{3}{5}[/tex]
[tex]1\frac{5}{6} - \frac{1}{6} = 1\frac{4}{6} = 1\frac{2}{3}[/tex]
[tex]8\frac{9}{14} - 2\frac{3}{14} = 6\frac{6}{14} = 6\frac{3}{7}[/tex]
[tex]\frac{1}{5} - \frac{1}{15} = \frac{3}{15} - \frac{1}{15} = \frac{2}{15}[/tex]
[tex]\frac{6}{7} - \frac{4}{5} = \frac{30}{35} - \frac{28}{35} = \frac{2}{35}[/tex]
[tex]5\frac{2}{3} - 2\frac{1}{7} = 5\frac{14}{21} - 2\frac{3}{21} = 3\frac{11}{21}[/tex]
[tex]9\frac{1}{12} - \frac{3}{4} = 9\frac{1}{12} - \frac{9}{12} = 8\frac{13}{12} - \frac{9}{12} = 8\frac{4}{12} = 8\frac{1}{3}[/tex]